2007
DOI: 10.1080/14768320701205218
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of coping, anxiety and glycemic control in adults with type 1 diabetes

Abstract: Diabetes is a unique disorder in how much it requires a high degree of individual self management strategies. Anxiety and stress can affect glycemic control, and thus management of emotions may be key to good glycemic control. This study is the first to examine how anxiety and coping style, and their interaction, can affect long-term glycemic control. We measured anxiety, coping, and HbA1C, a measure for mean blood glucose levels in the previous 6-8 weeks, in 115 patients with Type 1 diabetes at baseline and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…The assessment of coping styles, in addition to distress, was conducted because of their central role in the human stress process, and specifically their influence on the individual's emotional reactions to demanding/stressful experiences, including disease [13]. Indeed, in diabetes, the interaction between coping style and psychological distress has been shown to influence glycaemic control [14][15][16]. Our secondary aims included: (1) an examination of the effects of distress and coping style on an additional healing outcome, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of coping styles, in addition to distress, was conducted because of their central role in the human stress process, and specifically their influence on the individual's emotional reactions to demanding/stressful experiences, including disease [13]. Indeed, in diabetes, the interaction between coping style and psychological distress has been shown to influence glycaemic control [14][15][16]. Our secondary aims included: (1) an examination of the effects of distress and coping style on an additional healing outcome, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Better coping with these affective and stressful aspects of diabetes treatment will likely result in better behavioral adherence to the treatment regimen and subsequently better glycemic control. Support for this link has been found in the adult literature as a recent study found that a coping style that promoted better emotion regulation was associated with better glycemic control (25). However, to date, no study has examined the extent to which adolescents' emotion regulation skills relate to treatment adherence and glycemic control.…”
mentioning
confidence: 95%
“…The psychological prediction models tested had moderate predictive power of HbA 1c response to DAFNE, and this may have been limited because some of the predictors of DAFNE response were not collected or are not observable. Other variables such as personality factors 25,36 or attitudes toward the DAFNE course 37 could have provided additional predictive power to the regression models. Combining more detailed information from future psychological questionnaire data collected from DAFNE graduates with published qualitative findings [38][39][40] would allow the psychological prediction models to be refined.…”
Section: Discussionmentioning
confidence: 99%